2005
DOI: 10.1007/s00417-004-1121-6
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of indocyanine green, infracyanine green, and trypan blue on the human retinal pigmented epithelium

Abstract: Despite thorough rinsing after application, significant amounts of the not sufficiently water soluble indocyanine and infracyanine green are retained after surgery by the eye. Trypan blue, being more water-soluble than ICG, is probably retained to the least degree. This circumstance is fortunate given that trypan blue exhibits a chronic cytotoxicity comparable to ICG at all clinically relevant concentrations. During vitrectomy, surgeons should aim to expose retinal tissue to only low concentrations of these st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 44 publications
2
59
1
2
Order By: Relevance
“…Besides this, the stability of fluorochromes both in vitro and in vivo is critical, as opsonization and rapid clearance can greatly limit their application for in vivo imaging 11 . Other effects such as poor stability and low sensitivity or cytotoxic effects on target organs as seen with indocyanine green (ICG) [12][13][14][15][16] , are unwanted and must be taken into consideration when designing probes for in vivo imaging. These observations have led to the active development of several preclinical NIR fluorochromes, nanoparticles as well as new techniques for the in vivo imaging of inflammatory processes, cancer and for image-guided surgery 2.…”
Section: Introductionmentioning
confidence: 99%
“…Besides this, the stability of fluorochromes both in vitro and in vivo is critical, as opsonization and rapid clearance can greatly limit their application for in vivo imaging 11 . Other effects such as poor stability and low sensitivity or cytotoxic effects on target organs as seen with indocyanine green (ICG) [12][13][14][15][16] , are unwanted and must be taken into consideration when designing probes for in vivo imaging. These observations have led to the active development of several preclinical NIR fluorochromes, nanoparticles as well as new techniques for the in vivo imaging of inflammatory processes, cancer and for image-guided surgery 2.…”
Section: Introductionmentioning
confidence: 99%
“…This could explain why in cadaver eyes, IfCG as well as ICG followed by illumination may alterate the cleavage plane at inner retinal layers of the ILM (32) . Therefore, although IfCG and ICG may facilitate ILM removal, they may produce undesired retinal alterations in the neurosensorial retina, RPE and lead to visual field defects (32,33) . In summary, a safer IfCG profile may make it a better alternative than ICG for chromovitrectomy in humans, since IfCG in the concentration of 0.5 mg/ml allows ILM identification with fewer toxic effects.…”
Section: Infracyanine Greenmentioning
confidence: 99%
“…An ex vivo study of porcine retina suggested that exposure of 0.15% TB for 1 min did not cause any histological damage. 63 Using cultured human retinal pigment epithelial cells, no increase in cell death was found in concentrations up to 0.5% for 5 min, 64,65 however, prolonged culture for 6 days at even 0.005% resulted in toxicity. 65 Luke et al 66 found that exposure of bovine retina to 0.15% TB for more than 15 s caused a reduction in b-wave amplitude, which was only partially reversible after 115 min.…”
Section: Safetymentioning
confidence: 99%
“…63 Using cultured human retinal pigment epithelial cells, no increase in cell death was found in concentrations up to 0.5% for 5 min, 64,65 however, prolonged culture for 6 days at even 0.005% resulted in toxicity. 65 Luke et al 66 found that exposure of bovine retina to 0.15% TB for more than 15 s caused a reduction in b-wave amplitude, which was only partially reversible after 115 min. In animal studies, intravitreal injection of 0.2 and 0.06% TB into rabbit eyes that had undergone vitrectomy and gas injection showed sectoral damage to multiple retinal layers histologically, although no full-field ERG changes were detected.…”
Section: Safetymentioning
confidence: 99%